Synthesis and Characterization of Biodiesel from Tofu Dregs Oil through Esterification and Transesterification Irradiated by Microwave - Niyar Candra Agustin; Ricka Prasdiantika; Yustika Kusumawardani (Universitas Diponegoro, 2021)
Biodiesel has become an alternative energy source that continues to be developed. In this research, biodiesel synthesis from tofu dregs oil has been carried out through two stages of the reaction, namely the esterification stage using H2SO4 catalyst to reduce the content of FFA (Free Fatty Acid) and the transesterification stage using KOH catalyst to produce biodiesel. The esterification reaction using 2% H2SO4 catalyst was carried out by microwave heating at power variation of the microwave power 150, 300, 450, 600, 800 Watt with a reaction time of 10 minutes. The transesterification reaction was carried out with variations in microwave power of 150, 300, 450, 600, 800 watts and variations of the reaction time of 5, 10,15,20, and 25 minutes. Biodiesel products were characterized using Gas Chromatography-Mass Spectroscopy (GC-MS), Hydrogen-1 Nuclear Magnetic Resonance (1H-NMR) spectrometer, and feasibility test with the American Standard for Testing Material (ASTM). The characterization results showed that tofu dregs oil biodiesel has been successfully synthesized. The optimum biodiesel was achieved at 600 Watt microwave power with a reaction time of 20 minutes at 92%. The formation of biodiesel is evidenced by several methyl ester peaks, namely methyl oleate (59.98%), methyl linolenic (28.13%), methyl palmitate (8.54%), and methyl stearate (2.32%). Based on the results of ASTM biodiesel tofu dregs oil has met SNI-04-7182-2006 standards, namely the specific density parameter 60/60 ° F (0.87 g/cm3), kinematic viscosity at 40 ° C (4.3 mm2/s), pour point (8 °C), flash point (202 °C) and cloud point (7 )° C for biodiesel.